Storage and Preservation of Water Samples for Chemical Analysis - Amani Alalem; Fatih Eltaboni; Mohamed Elhuni; Nabil Bader; Nessma Alshelmani; Barbara Zimmermann (African Journal of Advanced Pure and Applied Sciences, 2026)
Sample storage and preservation are important steps in water chemical analysis. There are many changes may occur during the sample storage step. To minimize changes between sample collection and the analysis some probable problems have been discussed and some recommendations for sample preservation e.g. chemical additions, temperature control, choice of sampling container and holding time have been given.